2003
DOI: 10.14411/fp.2003.048
|View full text |Cite
|
Sign up to set email alerts
|

Neoechinorhynchus (Neoechinorhynchus) zabensis sp. n. (Acanthocephala: Neoechinorhynchidae) from freshwater fish in northern Iraq

Abstract: Abstract. Neoechinorhynchus (Neoechinorhynchus) zabensis sp. n. (Acanthocephala: Neoechinorhynchidae) is described from Capoeta damascina (Valenciennes, 1842) (type host) and Capoeta trutta (Heckel, 1843) in the Greater and Lesser Zab Rivers, northern Iraq. The new species is unique among all other species of the genus by its characteristic paired para-vaginal muscular appendage and fragmented giant nuclei in the lemnisci. Eleven of the other 88 valid species of Neoechinorhynchus and N. zabensis have middle a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 1 publication
3
16
0
Order By: Relevance
“…This study confirms the host specificity of N. zabensis as being to the genus Capoeta and extends it to include the species C. erhani and C. angorae, both of which have habitat and dietary requirements congruent within other members of the genus. The prevalence and intensity of infection of C. erhani with N. zabensis were high (76.9%, 1-180) and are similar to those reported for Capoeta trutta (Heckel, 1843) and Capoeta umbla (Heckel, 1843), although not as high as those reported for Capoeta damascina (Valenciennes, 1842) from Iraq and Capoeta barroisi Lortet, 1849 from the Murat River in Turkey (Amin et al, 2003b;Oguz et al, 2012;Koyun, 2012), suggesting that N. zabensis is well established in the Kahramanmaras Region. By contrast, the prevalence and intensity of infection (3.3%, 1-46) found in C. angorae were the lowest, suggesting that N. zabensis is rare in this host (Amin et al, 2003a, b;Oguz et al, 2012;Koyun, 2012).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…This study confirms the host specificity of N. zabensis as being to the genus Capoeta and extends it to include the species C. erhani and C. angorae, both of which have habitat and dietary requirements congruent within other members of the genus. The prevalence and intensity of infection of C. erhani with N. zabensis were high (76.9%, 1-180) and are similar to those reported for Capoeta trutta (Heckel, 1843) and Capoeta umbla (Heckel, 1843), although not as high as those reported for Capoeta damascina (Valenciennes, 1842) from Iraq and Capoeta barroisi Lortet, 1849 from the Murat River in Turkey (Amin et al, 2003b;Oguz et al, 2012;Koyun, 2012), suggesting that N. zabensis is well established in the Kahramanmaras Region. By contrast, the prevalence and intensity of infection (3.3%, 1-46) found in C. angorae were the lowest, suggesting that N. zabensis is rare in this host (Amin et al, 2003a, b;Oguz et al, 2012;Koyun, 2012).…”
Section: Discussionsupporting
confidence: 77%
“…Neoechinorhynchus zabensis was originally described from species of Capoeta in tributaries of the Tigris and Euphrates rivers in Iraq, and the geographic distribution has subsequently been extended to tributaries in Iran and Turkey (Amin et al, 2003b;Oguz et al, 2012;Koyun, 2012). Oguz et al (2012) concluded that N. zabensis was restricted to the Tigris/Euphrates river system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…N. agilis is a misidentification of N. iraqensis [106]. The first report of N. iraqensis was as species de novo from the intestine of L. abu from the Euphrates River at Al-Fallujah region [107], while its description was given later by Amin et al [108]. N. iraqensis and the misidentified N. agilis have so far 24 fish host species in Iraq [17].…”
Section: Major Groups Of Parasitic Fauna: Parasite-host Listmentioning
confidence: 99%
“…Leptomelanosoma indicum Shaw, 1804 is one of the polynemid fish occurring mainly over shallow muddy and sandy bottoms of the Continental shelf occasionally enters the river and rare beyond a depth of 60 m. These fishes are carnivorous in habit feeding mainly on small benthic crustaceans like prawns, crabs and small fishes which serve as primary intermediate hosts for the various metazoan parasites. Neoechinorhynchus is a freshwater acanthocephalan genus mostly reported from various freshwater and brackish water fishes worldwide (Rudolphi 1808;Linton 1889Linton , 1932Luhe 1911;Bhalerao 1936;Yamaguti 1939Yamaguti , 1963Bullock 1963;Golvan 1969;Nickol and Thatcher 1971;Eure 1976;Chandra et al 1984;Ching 1984;Amin and Vignieri 1986a, b;Durborow et al 1988;Amin and Gunset 1992;Buckner and Buckner 1993;Hoffman 1999;Amin 2002;Amin et al 2003;Santos et al 2005;Elsayed and Faisal 2008;Rueckert et al 2008;Amin and Heckmann 2009;Amin andMuzzall 2009 andSalgado et al 2010). Reports of Neoechinorhynchus in marine fishes are very exceptional (Podder 1937;Yamaguti 1939;Chandra et al 1984;Amin et al 2002;Amin andChristison 2005 andJuan andAguirre 2005).…”
Section: Introductionmentioning
confidence: 99%